(3JfejI GdehGQO GdHTQjI GdYQHjI hSjGSGJ Ndb aQU Yed LOjOI (B/s - (3bhjOQ, EHQGgjes ([(3Ohf ecGf(B]: s [(3Ohf fGTQ(B], s)
(3efGN GdGSJKeGQ aj GdOhd GdYQHjI,eSJbHd Gdbhi GdYGedI GdYQHjI,CgejI GdJYdje hGdJOQjH Gdegfj aj HQGeL GdJfejI GdHTQjI,hSGFd hBdjGJ JfejI GdehGQO GdHTQjI,GdSjGSGJ GdeJWhQI dNdb aQU Yed LOjOIs
Keywords: (3EOGQI GdCaQGOs; (3GdGSJKeGQs